Individual Auditor Turnover and Audit Quality—Large Sample Evidence from U.S. Audit Offices - Ma, Tao; Wan, Chi; Wang, Yakun; Zhao, Yuping (The Accounting Review, 2024)
ABSTRACT We examine the relationship between audit quality and office-level auditor turnover. Using resumes of over 106,000 Big 4 auditors, we find that audit offices with higher turnover have a greater likelihood of client annual report restatements. This detrimental effect is more pronounced when the departing auditors are more experienced and when the office faces tighter human capital constraints and is primarily attributable to voluntary turnover. Further, such negative effect is borne mostly by complex clients and intangible-intensive clients but is weakened for clients with greater product similarity to the client portfolio of the audit office. Last, the impact of office-level turnover on audit quality persists after controlling for firm-level turnover. Our findings inform the current policy debate on whether and to what extent audit firms should disclose auditor turnover as a potential indicator of audit quality. Data Availability: Data are available from the public sources cited in the text. JEL Classifications: M42.